One‐Step Synthesis of Photoaffinity Probes for Live‐Cell MS‐Based Proteomics. Issue 71 (14th September 2021) - Fallon, David J.; Lehmann, Stephanie; Chung, Chun‐wa; Phillipou, Alex; Eberl, Christian; Fantom, Ken G. M.; Zappacosta, Francesca; Patel, Vipulkumar K.; Bantscheff, Marcus; Schofield, Christopher J.; Tomkinson, Nicholas C. O.; Bush, Jacob T.
Abstract: We present a one‐step Ugi reaction protocol for the expedient synthesis of photoaffinity probes for live‐cell MS‐based proteomics. The reaction couples an amine affinity function with commonly used photoreactive groups, and a variety of handle functionalities. Using this technology, a series of pan‐BET (BET: bromodomain and extra‐terminal domain) selective bromodomain photoaffinity probes were obtained by parallel synthesis. Studies on the effects of photoreactive group, linker length and irradiation wavelength on photocrosslinking efficiency provide valuable insights into photoaffinity probe design. Optimal probes were progressed to MS‐based proteomics to capture the BET family of proteins from live cells and reveal their potential on‐ and off‐target profiles. Abstract : Get PALs quick : A multicomponent reaction for the one‐step synthesis of PAL probes. A library of diverse bromodomain (BET)‐targeting PAL probes was synthesized and profiled extensively (physicochemical properties, biochemical and cellular activities, photolabeling efficiencies and crystallographic studies). Optimal probes were profiled by MS‐based proteomics to capture BET proteins from live cells and reveal their potential on/off‐target profiles. We envisage that this methodology can be used to quickly access PAL probes for other compounds‐of‐interest and obtain their target profiles.